2022
DOI: 10.3390/ani12182418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fructus mume and Scutellaria baicalensis Georgi on the Fecal Microbiota and Its Correlation with Apparent Nutrient Digestibility in Weaned Piglets

Abstract: Traditional Chinese medicine (TCM) has long been demonstrated to exert a therapeutic effect on various diseases and has been used as a substitute for antibiotics in pig production. However, few studies have investigated the relationship between the intestinal microbiota and apparent nutrient digestibility when weaned piglet diets are supplemented with TCM. One hundred and sixty-two 25-day-old weaning piglets were housed in an environmentally controlled nursery facility and fed a basal diet (control group, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Similarly, a bidirectional solid fermentation of Scutellaria baicalensis Georgi using the medicinal fungus Ganoderma lucidum has enabled the isolation of 6-o-β-D-glucose-cyclo astragalus alcohol from the product ( 36 ). Lactobacillus plantarum and Lactobacillus rhamnosus ( 37 ) have been shown to be effective in increasing the weight of piglets, reducing the diarrhea rate, improving immunity, and regulating the intestinal microbiota of piglets when used as a feed additive made from fermented Scutellaria baicalensis Georgi residue ( 38 ). Further, Yang et al ( 39 ) demonstrated that the product obtained from the fermentation of Scutellaria baicalensis Georgi dregs with Trichoderma echinococcus had strong antibacterial activity against Proteus , Salmonella, Bacillus subtilis , Staphylococcus aureus , and Escherichia coli , with an inhibition zone diameter of 19.1–29.9 mm, but no antibacterial effect was observed with the Scutellaria baicalensis Georgi dregs and Trichoderma echinococcus mixture.…”
Section: Advantages Of Traditional Chinese Medicine Fermented By Prob...mentioning
confidence: 99%
“…Similarly, a bidirectional solid fermentation of Scutellaria baicalensis Georgi using the medicinal fungus Ganoderma lucidum has enabled the isolation of 6-o-β-D-glucose-cyclo astragalus alcohol from the product ( 36 ). Lactobacillus plantarum and Lactobacillus rhamnosus ( 37 ) have been shown to be effective in increasing the weight of piglets, reducing the diarrhea rate, improving immunity, and regulating the intestinal microbiota of piglets when used as a feed additive made from fermented Scutellaria baicalensis Georgi residue ( 38 ). Further, Yang et al ( 39 ) demonstrated that the product obtained from the fermentation of Scutellaria baicalensis Georgi dregs with Trichoderma echinococcus had strong antibacterial activity against Proteus , Salmonella, Bacillus subtilis , Staphylococcus aureus , and Escherichia coli , with an inhibition zone diameter of 19.1–29.9 mm, but no antibacterial effect was observed with the Scutellaria baicalensis Georgi dregs and Trichoderma echinococcus mixture.…”
Section: Advantages Of Traditional Chinese Medicine Fermented By Prob...mentioning
confidence: 99%
“…MF, composed of organic acids, flavonoids and fatty acids, used to treat chronic cough, prolonged diarrhea, and other inflammation-related diseases (8). Previous studies have shown that weaned piglets fed with antibiotic-free diets supplemented with MF gained more weight and were healthier by modifying the gut microbial composition (9). CC is a Chinese herbal medicine with strong anti-inflammatory activity, and has obvious clinical medicinal value.…”
Section: Introductionmentioning
confidence: 99%